HUBUNGAN NILAI KURS DENGAN INDEKS HARGA SAHAM PERTANIAN DI INDONESIA - Vania Jessica Tedjamulia; Sahala Manalu; Rony Joyo Negoro Octavianus (University of Merdeka Malang, 2013)
This study was conducted to test the independent variable exchange rate USD/IDR, EUR/IDR, JPY/IDR, andthe dependent variable agricultural stock index during five years (2008-2012). Sampling technique used waspurposive sampling method. Data analysis technique used was Auto Regressive Distributed Lag (ARDL)proposed by Pesaran et al. (2001) in order to investigate the order of co-integration. Hypothesis test used wasF-test to test the simultaneous effect and t-test for testing the partial regression coefficient with a significancelevel of 5%. F-test results indicated that exchange rate of USD/IDR, EUR/IDR, and JPY/IDR gave significanteffect on agriculture stock index. The t-test results indicated that the variable exchange rate of USD/IDR, EUR/IDR and JPY/IDR gave partially significant effect on agricultural stock index period 2008-2012. Adjusted Rsquare (R2) was 7,8%. The statistical results of Auto Regressive Distributed Lag indicated that changes inUSD/IDR and JPY/IDR were negatively related to changes in stock price index of agriculture. EUR/IDR hada positive impact to the stock price index of agriculture